A Canadian Perspective: French Language Learning. Issue 4 (October 2020) - Ryan, Thomas G.; Sinay, Erhan
In Canada, language learning is viewed as an international, national and local need. Herein an international perspective is provided that guides the reader into a National language perspective which is uniquely Canadian. For instance, within Ontario there are concerns about French language education and the multiple entry points for students and inequities in most school boards in Ontario. The fact that School Boards across the province have identified the supply and demand for Ontario elementary and secondary teachers as variable especially in certain subjects such as French Language is unsettling. Future recruitment needs to cast a wide net and move deep into Faculties of Education in a proactive manner. Having the necessary French teachers and support staff is very important yet the need to retain students and educators in French programs is equally essential since retention and attrition rates impact program viability. Recent history in Ontario Core French (CF) programs demonstrate reduced enrollments over time therefore the government of Ontario has acknowledged a need to increase FSL student retention via improved access, training, relationships and special programs, to ensure students are enrolled and retained as long as possible.